Biomorphic Clothing Sculpture Interface as an Emotional Communication Space - Yoo, Young Sun; Cho, Minjin; Eum, Jung Sun; Kam, Seon Ju (Frontiers in Psychology, 2020)
This study found that clothing, combined with digital technology, can be a wearable computer that adapts to environmental change and increases biological limits, as well as an emotional space to which art and design are applied and that promotes mutual communication. A user-friendly interface is proposed for those pursuing a new artistic experience by building a conceptual algorithm for biomorphic clothing sculpture modeling that can be used to create generative designs simply by entering moderated mediator variables. Biomorphic clothing sculpture refers to clothing that is inspired by life in nature and modeled in three dimensions. As the human body and buildings are 3D forms, the parametric design method used frequently in architecture is implemented here and used as a tool to explore attributes and representations of 3D modeling in clothing sculpture design. On the basis of a literature review, this study presents knowledge-based data for biomorphic clothing sculpture that can predict generative design outcomes, and through a case study, identifies the mediator variables and attributes of the parametric process related to biomorphic clothing sculpture modeling. The knowledge-based data on biomorphic clothing sculpture and biomorphic clothing sculpture modeling mediator variables discovered during the research are applied to the 3D modeling process as visual data and presented as the conceptual interface of biomorphic clothing sculpture.